Engaging Secondary Students in Collaborative Action-Oriented Inquiry: Challenges and Opportunities - J. Spencer Clark (Networks: An Online Journal for Teacher Research, 2017)
I recently helped facilitate a collaborative problem-based inquiry project with eighty-three secondary students. The students attended a large high school situated in a medium size town, surrounded by farmland and smaller rural towns. Demographically, nearly half of the students identified as Latina/o, while the slight majority of the students were White. The two groups of students also identified with the two dominant religious communities in the area: Catholic and Church of Jesus Christ of Latter Day Saints. The students were all seniors in an advanced American Government course.